2014
DOI: 10.1186/1746-6148-10-83
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of porcine reproductive and respiratory syndrome virus (PRRSV) genotypes in Ontario, Canada, 2004–2007

Abstract: BackgroundThe spread of PRRSV among pig herds has been investigated experimentally, but few observational studies have investigated this subject. Because PRRSV is endemic and live modified vaccines are used in Ontario, the spatial and temporal distributions of 6 PRRSV genotypes were investigated in the province during the period from 2004–2007. The purpose was to find evidence of spread of PRRSV genotypes and determine if spread could be attributed to supplier or ownership connections between herds. Sequence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 21 publications
3
41
0
1
Order By: Relevance
“…To the best of our knowledge very few models have been published to predict PRRS status in the US swine industry. A study conducted by [17] in Ontario, Canada investigated evidence of spread of PRRSV genotypes and determined if spread could be attributed to supplier or ownership connections between herds. The spatial and temporal distributions of six PRRSV genotypes were investigated from 2004 to 2007.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge very few models have been published to predict PRRS status in the US swine industry. A study conducted by [17] in Ontario, Canada investigated evidence of spread of PRRSV genotypes and determined if spread could be attributed to supplier or ownership connections between herds. The spatial and temporal distributions of six PRRSV genotypes were investigated from 2004 to 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a molecular study in Canada, Thakur et al [102] found that the predominant relationship between strains within a cluster were the introduction of infected pigs into farms. Also in Canada, Kwong et al [103] and Rosendal et al [104] identified the source of gilts as one of the main causes for explaining the spread of different strains in the country.…”
Section: Prrsv Transmission Between Farmsmentioning
confidence: 99%
“…140 Others have involved broad classifications based on PRRSV types (European vs North American) on the basis of serologic results, 77 genotypes on the basis of RFLP patterns, 35,141 classification based on phylogenetic trees and different cutoff points to categorize variants into groups, 40,41,142 or matrices of similarities to assess correlations between the similarity of nucleotide sequences and spatial and other proximities among herds. Some studies relied on serologic evidence of PRRSV circulation in various herd types.…”
Section: Control and Elimination Programs At The Farm Levelmentioning
confidence: 99%
“…145 As a part of such investigations, one of the largest uncertainties continues to be importance of area spread (also commonly referred to as local spread), which is often discussed in the context of airborne transmission. Furthermore, several authors reported the possibility of area spread for some discrete genotypes, although such spread was not identified as the dominant mechanism of spread 41,141 or could be explained in some cases because of common sources of animals. In other studies, 35,140 existence of area spread could not be identified.…”
Section: Control and Elimination Programs At The Farm Levelmentioning
confidence: 99%
See 1 more Smart Citation